Dasboard dan Visualisasi Reservasi Buka Puasa di Hotel XYZ Menggunakan Looker Studio & Google Form - Anggi Hadi Wijaya; Ipriadi; Wahyu Fitri (CV. ITTC INDONESIA, 2024)
Hotel XYZ is a hotel in the city of Padang which operates in the accommodation and restaurant sector. With the arrival of the holy month of Ramadhan, usually every hotel always offers attractive promotions, especially at breaking the fast together at the hotel. Breaking the fast together has become a routine tradition every Ramadan by community agencies, families and sometimes even individuals breaking the fast outside the home. The Marketing Department is a department that has the function and task of promoting hotels, especially during fast breaking events at hotels during the month of Ramadan. The Marketing Department has a very important role and function in the Hotel, so an information dashboard is really needed that can display Performance Reports and Graphs from the Marketing Department. Using Looker Studio Visualization and Google Form as Input for Iftar Reservations can speed up the information process, decisions and measure performance.